2012
DOI: 10.1002/cbf.2820
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 protects H2O2‐induced cardiomyocytes injury through upregulation of prohibitin via STAT3 phosphorylation

Abstract: Our results provide direct evidence that prohibitin is a protective factor of IL-6 preconditioning in H(2)O(2)-induced neonatal rat ventricular cardiomyocytes death. The upregulation of prohibitin by IL-6 is, at least, partially regulated through STAT3 phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…To further explore the involved molecules in apigenin-induced apoptosis in OxLDL-loaded MPMs, two-dimensional electrophoresis (2-DE) and mass spectrometry were performed as described previously [ 23 ]. Twenty-eight proteins were identified successfully including fourteen downregulated spots and fourteen upregulated spots caused by OxLDL ( Figure 3(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the involved molecules in apigenin-induced apoptosis in OxLDL-loaded MPMs, two-dimensional electrophoresis (2-DE) and mass spectrometry were performed as described previously [ 23 ]. Twenty-eight proteins were identified successfully including fourteen downregulated spots and fourteen upregulated spots caused by OxLDL ( Figure 3(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggests that IL-6 provides protection against colitis via a mechanism dependent on Stat3 activation in the intestinal epithelium [56]. We and others have shown that IL-6 increases expression of PHB through Stat3 transcriptional activation to promote survival of IECs, cardiomyocytes, and hepatocytes [53-55, 57]. IL-6 protective effects in cardiomyocytes are dependent upon IL-6 induction of PHB [58] and phosphorylation of mitochondrial S727-Stat3 [59].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is a potent reactive oxygen species that causes mitochondrial dysfunction and cell death. Preconditioning cells with IL-6 decreases H 2 O 2 -induced cell death by increasing the expression of prohibitin, which is involved in mitochondrial biogenesis and metabolism, apoptosis and replicative senescence [137]. In addition to signalling through STAT-3, the stress-induced activation catalase.…”
Section: Maintenance Of Redox Potentialmentioning
confidence: 99%